Apical stress redistribution during anterior vertebral body tethering for thoracic adolescent idiopathic scoliosis: a finite element analysis of a novel surgical technique - Mac-Thiong, Jean-Marc; Hachem, Bahe; Clin, Julien; Le Naveaux, Franck; Parent, Stefan (Spine deformity, 2025)
Purpose Apical stress redistribution (ASR) is proposed to mitigate failure risks after anterior vertebral body tethering for adolescent idiopathic scoliosis. It consists in releasing set-screws at peri-apical levels following curve tensioning to redistribute stresses within the construct. This study determines the biomechanical impact and curve correction obtained with ASR. Methods Finite element models of anterior vertebral body tethering were constructed for three typical scoliotic patients with Lenke 1 curves. ASR was simulated by releasing tension on the cable at the level of the three apical set screws (i.e. untightening three consecutive periapical set screws), followed by retightening of the set screws without further tensioning. Cable tension, implant forces and spine geometry were compared before and after performing ASR. Results Periapical cable tension decreased post-ASR, and ASR also reduced the maximum tensions proximally and distally. Postoperative disc height was similar between conventional and ASR approaches. Apical intervertebral disc stresses were shifted from concave to convex compression intra and postoperatively, with a similar pattern between the conventional and ASR techniques. The ASR technique achieved scoliotic curve corrections of 54%, 68%, and 79%, while the conventional technique resulted in corresponding corrections (54%, 68%, and 80%) for subjects 1, 2, and 3. The periapical coronal curves exhibited similar patterns. Conclusion ASR demonstrated promising apical cable and implant forces re-equilibrium compared to the conventional approach. This novel technique did not impair immediate and postoperative curve correction, while maintaining similar apical intervertebral stress distribution. ASR shows potential to modulate growth while reducing maximum cable tension infra- and supra-apical.